Implementasi Pembuatan Label Kemasan Dan Digital Marketing Dalam Pengembangan Teknologi UMKM Di Kelurahan Bendo Kota Blitar - Dewi Puspa Arum; Indah Sari Dwi Agustin; Hendrik Cahyono; Rizky Rianto; Santi Eka Rahmawati; Fajerul Dicky Saputra; Ardhelia Damayanti Wirawan (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
The aim of this digital marketing training activity is to increase participants' knowledge in terms of utilizing digital platforms, as well as provide alternative livelihood options for participants to increase their income. Therefore, the identity of the product itself is needed in the industrial era 4.0. This research method was carried out offline using two sessions, namely, an explanation regarding labeling and digital marketing and practicing how to make labels. Therefore, KKN students carry out a work program in the form of regular assistance to MSME business actors related to making labels to make attractive packaging. The training for labeling and digital marketing has gone according to the wishes and expectations of two parties, namely the owner of the Soybean Crackers